Pulse gasification and hot gas cleanup apparatus and process - MANSOUR MOMTAZ N; CHANDRAN RAVI (2006)
A gasifier system and process comprises a pulse combustion device in communication with a fluid channel for producing a gas stream having heat or fuel value. The pulse combustion device is operated under sub-stoichiometric conditions such that combustion and steam reforming both occur in the fluid channel. The pulse combustion device also produces a pulsating combustion product stream and an acoustic pressure wave. The acoustic pressure wave serves to cause agglomeration of particles contained within the combustion stream for easy removal. In one embodiment, a sulfur capturing agent is injected into the fluid channel for not only removing sulfur from the combustion product stream but for also facilitating particle agglomeration. Ultimately, a gas stream containing hydrogen is produced that may be used in various processes, such as in the production of electricity.